Store køretøjers forbrug af motorvejes kapacitet - Sørensen, Henning (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
This paper describes an investigation of the effect vehicle composition has in traffic flow on Danish freeway sections. The objective involved the establishment of actual passenger car equivalent values for many vehicle types. The study comprises 4- and 6-lane freeways on level terrain. The study has been concentrated on capacity situations. The methodology used is based on time headways between the vehicles. The time lag between the rear of the preceding vehicle to the rear of the vehicle is directly related to the capacity consumption of the vehicle. The vehicle length and the chassis height are measured, making it possible to classify and group the vehicles. Statistical analysis of the measurements has been car-ried out and the average values of gap and passage time for a given group of vehicles are related to the same values for passenger cars. Among the results are that passenger car equivalents depend on the size of the vehicle and on the speed of the traffic flow. The passenger car equivalent equals 2 for a single-unit truck on a 4-lane freeway up to 3 for a tractor-trailer truck on a 6-lane freeway.